Development of small and medium-sized enterprises in the Malaysia plans: Some insights - Hashim, Mohd Khairuddin (UUM Press, 2011)
The development of small and medium-sized enterprises (SMEs) in Malaysia has been emphasized in the country's five-year development plans. Since the First Malaysia Plan (1966 to 1970), various policies, development plans and programmes have been introduced to help sustain the development as well as the growth of SMEs in the national economy.The literature review however indicates that the development of SMEs as featured in the ten Malaysia Plans has not received much attention. This paper attempts to provide some insights into the development of SMEs in the First Malaysia Plan (1966 to 1970) through the Tenth Malaysia Plan (2011-2015).